Public debt sustainability and the impact of the COVID-19 pandemic: the case of Latvia - Vitols, Edgars; Jekabsone, Sandra (University of Latvia, 2021)
The Covid-19 pandemic has had a significant impact on economic growth. Many countries are trying to stimulate their economies and help their citizens through fiscal policy, which have led to a significant increase in government debt. A significant increase in Latvia's general government debt is also being forecasted. Excessive debt threatens the sustainability of public finances and has a negative impact on the country's economic growth. The aim of this study is to assess the sustainability of general government debt in Latvia, taking into account the impact of the Covid-19 pandemic. The results of the study show that the increase in Latvia's general government debt as a result of the Covid-19 pandemic is not considered to be a threat to government debt sustainability; according to the authors' forecasts, general government debt will decrease over time if the general government structural deficit does not exceed 2.2% of GDP or the primary deficit does not exceed 1.3% of GDP.
Keywords: debt sustainability; Covid-19; fiscal policy; Research Subject Categories::SOCIAL SCIENCES